2011
DOI: 10.1111/j.1574-695x.2011.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal immunization of mice withLactobacillus caseiexpressing the pneumococcal surface protein C primes the immune system and decreases pneumococcal nasopharyngeal colonization in mice

Abstract: Streptococcus pneumoniae colonizes the upper respiratory tract of healthy individuals, from where it can be transmitted to the community. Occasionally, bacteria invade sterile niches, causing diseases. The pneumococcal surface protein C (PspC) is a virulence factor that is important during colonization and the systemic phases of the diseases. Here, we have evaluated the effect of nasal or sublingual immunization of mice with Lactobacillus casei expressing PspC, as well as prime-boosting protocols using recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…route in mice has been described, especially for animal models of allergy (44,65,66). However, the use of this route for vaccination, using recombinant lactic acid bacteria expressing heterologous antigens, has been less explored (22).…”
Section: Discussionmentioning
confidence: 99%
“…route in mice has been described, especially for animal models of allergy (44,65,66). However, the use of this route for vaccination, using recombinant lactic acid bacteria expressing heterologous antigens, has been less explored (22).…”
Section: Discussionmentioning
confidence: 99%
“…This vector contained a spaX gene product as an anchor to express antigens on the cell wall. The spaX is considered a good choice for surface expressing in L. casei [19,29]. Meanwhile, the expression of susceptible antigens for mucosal immunization with live vectors can elicit a better immune response when the expressed proteins anchor to a cell wall [10,32,38].…”
Section: Discussionmentioning
confidence: 99%
“…The pellets were suspended in a lysis buffer (50 mM Glucose, 25 mM Tris-HCl, 10 mM EDTA, 20 mg/ml Lysozyme, pH 8.0) and exposed to three consecutive freeze-thaw cycles. The protein fractions were processed as previously described [29,30].…”
Section: Protein Expressionmentioning
confidence: 99%
“…Attenuated pathogens or LAB have been engineered to function as vaccine delivery vehicles against pathogens including Yersinia pseudotuberculosis [27], Salmonella Typhimurium [28,29], and Pneumococcal nasopharyngeal [30,31]. One particular study by Mohamadzadeh et al showed that a recombinant LAB vaccine could be as effective as a traditional injected vaccine in an animal model [32•].…”
Section: Engineering Strategies Targeting Bacterial Infectionmentioning
confidence: 99%